Associations Between Cognitive Performance and Self-Efficacy for Pain Management in Older Adults With Chronic Pain...2024 American Society for Pain Management Nursing (ASPMN) Annual Conference, October 16-19, 2024, San Antonio, TX. - Suyasith, Pornthip; Shi, Ling; Foust, Janice B.; You, Tongjian; Leveille, Suzanne G. (Pain Management Nursing, 2025)
Self-efficacy for pain management is the key to successful pain management, yet little is known about the effect of cognitive performance on self-efficacy for pain management. This study aimed to examine to what extent cognitive performance is related to self-efficacy for pain management in older adults with chronic pain. The analyses utilized data from the baseline assessment of the MOBILIZE Boston Study. Five neuropsychological tests—the Clock in the Box Test, Letter Fluency Test, Trail-making Test, Hopkins Verbal Learning Test, and WORLD Test—were performed to measure the cognitive performance domains of 458 participants, aged 70 years and reporting chronic pain and self-efficacy for pain management. We measured self-efficacy for pain management using the Chronic Pain Self-Efficacy Scale. Statistical analyses were done using multiple linear regression analysis. After adjusting for sociodemographic factors, general cognitive performance, executive function, as measured by the Clock in the Box Test, and attention, as measured by the Trail-Making Test Part A, were significantly associated with self-efficacy for pain management in older adults with chronic pain. However, after controlling for sociodemographic factors, chronic conditions, pain interference, and physical performance, the associations between cognitive performance measures and self-efficacy for pain management weakened. Greater cognitive performance in attention and executive function might be associated with better self-efficacy for pain management. Future longitudinal research is required to investigate the long-term implications of cognitive performance changes on the progress of self-efficacy for pain management in community-dwelling older adults.